Prehistoric sea reptiles : classify the features of prehistoric creatures - Newland, Sonya (Dino-sorted!, 2021)
Classify the features of prehistoric creatures! Take a trip back in time to meet the giant reptiles that ruled the prehistoric seas! Get a closer look at the features of different groups, from the semiaquatic nothosaurs and the streamlined ichthyosaurs of the Triassic Period, to the ferocious plesiosaurs, pliosaurs and mosasaurs of the Jurassicand Cretaceous Periods. Learn about classifying prehistoric creatures with the Dino-sorted! series. Get a close-up look at dinosaurs and other ancient beasts, with large colourful artwork, and discover the key features that they have in common.